Real-time effective-action approach to the Anderson quantum dot - Sexty, Dénes; Gasenzer, Thomas; Pawlowski, Jan M. (Arxiv, 2010)
The non-equilibrium time evolution of an Anderson quantum dot is investigated. The quantum dot is coupled between two leads forming a chemical-potential gradient. We use Kadanoff-Baym dynamic equations within a non-perturbative resummation of the s-channel bubble chains. The effect of the resummation leads to the introduction of a frequency-dependent 4-point vertex. The tunneling to the leads is taken into account exactly. The method allows the determination of the transient as well as stationary transport through the quantum dot, and results are compared with different schemes discussed in the literature (fRG, ISPI, tDMRG and QMC).